Ultra-processed food consumption and chronic kidney disease risk: a systematic review and dose–response meta-analysis - He, Xingzhen; Zhang, Xiaoyan; Si, Caijuan; Feng, Yuliang; Zhu, Qin; Li, Songtao; Shu, Long (Frontiers in Nutrition, 2024)
Background: High intake of ultra-processed food (UPF) has been associated with increased risk of chronic kidney disease(CKD), but the results remain inconsistent. We therefore performed this systematic review and dose-response meta-analysis of observational studies that shed light on the association between UPF consumption and the risk of CKD.Methods: A systematic literature search of PubMed, Embase, Web of Science, Scopus and China National Knowledge Infrastructure (CNKI) databases was carried out to find the eligible articles published up to October 31, 2023. Random-effects or fixed-effects models were used to pool the relative risks(RRs) and their 95% confidence intervals (CIs).The potential sources of heterogeneity across studies were examined using the Cochran's Q test and I-square(I 2 ). Publication bias was examined using the visual inspection of asymmetry in funnel plots and quantified by Begg's and Egger's tests.Results: Eight studies(six cohort and two cross-sectional studies) exploring the association between UPF consumption and risk of CKD, were included in the final analysis.The pooled analyses revealed that high consumption of UPF was associated with an increased risk of CKD (RR= 1.25; 95%CI: 1.09-1.42, P<0.0001). Moreover, a 10% increase of UPF consumption was associated with a 7% higher risk of CKD (RR=1.07; 95%CI: 1.04-1.10, P< 0.001). Dose-response analysis of all included studies showed a linear association between UPF consumption and the risk of CKD (RR=1.02; 95%CI:0.99-1.05, Pnonlinearity=0.843). Conclusions: Our findings indicate that high consumption of UPF is significantly associated with an increased risk of CKD. Future research with prospective design is required to confirm this positive 1 3 association.